Development of Control and Measurement Procedures for Geometrically Complex Surfaces - Alexandrov, Islam A.; Karpov, Nikita S.; Ivanov, Naur Z.; Lampezhev, Abas H.; Titova, Anastasia P. (Emerging Science Journal, 2025)
This study aims to develop and automate control and measurement procedures for parts with complex geometric surfaces under multiproduct manufacturing conditions. By integrating combinatorial analysis, statistical testing, and probe trajectory optimization into a unified framework, the proposed methodology formalizes measurement planning within an automated system. The actual dimensional characteristics of each workpiece are determined at the design stage, enabling the adaptation of the technological process to specific components. Experimental validation was performed on a FARO 9 ARM coordinate measuring machine using six types of complex parts, and statistical testing was performed to identify the optimal number of control points (108) with a minimum measurement time of 72 min per part. The methodology achieved a defect rate reduction of 5% and demonstrated an annual cost savings of 641,172 Rubles. This study integrates control point selection, probe trajectory planning, and measuring instrument choice into a single automated system that adapts to actual workpiece geometry, advancing Metrology 4.0 principles. The proposed approach significantly improves performance compared with conventional methods, reducing metrological preparation time by 76%, lowering defect rates by 50%, and decreasing the number of measurement operations by over 40%. These results confirm the potential of the methodology for enhancing productivity and economic efficiency in digital manufacturing environments.